Research on the correlation between clinical nurses’ self-efficacy, future time perspective, and occupational burnout - Xie, Daixun; Zhu, Xiaoqin; Zhang, Xiurong; Jiang, Zhaoquan; Wang, Xin; Liu, Tao (Frontiers in Public Health, 2024)
Background The number of clinical nurses in China experiencing professional burnout is increasing yearly, posing a serious challenge to the public health sector. Implementing effective intervention strategies is key to reducing the level of occupational burnout. At present, training aimed at alleviating occupational burnout among clinical nurses is very limited, with common training programs focusing on addressing external factors of occupational burnout rather than the internal cognitive issues of clinical nurses. Self-efficacy and future time perspective are both aspects of an individual’s internal self-cognition. Meanwhile, the relationship between clinical nurses’ self-efficacy, future time perspective, and occupational burnout is not clear, and further research is needed to verify this. Objective This study aims to reveal the relationship between clinical nurses’ self-efficacy, future time perspective, and occupational burnout, and to explore the mediating role of future time perspective between self-efficacy and occupational burnout among clinical nurses, providing a scientific reference for training directions to improve occupational burnout. Methods This study used a cross-sectional design, conducting a questionnaire survey with 529 practicing clinical nurses using the General Demographics Questionnaire (GDQ), the General Self-Efficacy Scale (GSES), the Zimbardo Time Perspective Inventory (ZTPI), and the Maslach Burnout Inventory-General Survey (MBI-GS). SPSS software version 26.0 was used to analyze the correlation between variables, and AMOS 26.0 was used to test the mediation effect. Results Clinical nurses’ self-efficacy had a negative predictive effect on occupational burnout (r = −0.503, p < 0.001). Future time perspective showed significant differences in regression coefficients on both the paths of self-efficacy (r = 0.615, p < 0.001) and occupational burnout (r = −0.374, p < 0.001). Future time perspective played a partial mediating role between self-efficacy and occupational burnout, accounting for 33.8% of the total effect. Conclusion This study suggests a significant correlation between clinical nurses’ self-efficacy, future time perspective, and occupational burnout. Self-efficacy can directly affect occupational burnout in clinical nurses and can also indirectly affect occupational burnout through the future time perspective.